Investigation of MWCNT Reinforcement on the Strain Hardening Behavior of Ultrahigh Molecular Weight Polyethylene - Hassan Mahfuz; Mujibur R. Khan; Theodora Leventouri; Efthymios Liarokapis (Journal of Nanotechnology)
We have investigated strain hardening behavior of ultrahigh molecular weight polyethylene (UHMWPE) reinforced with 2.0 wt% loading of multiwalled carbon nanotubes (MWCNTs). A solution spinning process was used to produce neat and MWCNT-reinforced filaments of UHMWPE. Tensile tests of filaments showed 62% and 114% improvement in strength and modulus, respectively. Strain hardening tests on filaments revealed spectacular contribution by MWCNTs in enhancing strength and modulus by more than one order of magnitude. SEM micrographs showed sufficient coating of nanotube surface with the polymer that promoted interface adhesion. This intimate interfacial interaction enforced alignment of nanotubes during repeated loading-unloading sequences and allowed effective load transfer to nanotubes. Close interaction between UHMWPE and nanotubes was further evidenced by Raman spectral distribution as a positive shift in the D-band suggesting compressive stress on nanotubes by lateral compression of polymer. Nanotubes thus deformed induced the desired strain hardening ability in the UHMWPE filament. Differential scanning calorimetry (DSC) tests indicated around 15% increase in crystallinity after strain hardening—which together with nanotube alignment resulted in such dramatic improvement in properties.